2017
DOI: 10.18632/oncotarget.15879
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide suppresses thein vitroandin vivogrowth of lung cancer cells by targeting hyaluronan-CD44/RHAMM signaling

Abstract: Higher levels of hyaluronan (HA) and its receptors CD44 and RHAMM have been associated with poor prognosis and metastasis in NSCLC. In the current study, our goal was to define, using cellular and orthotopic lung tumor models, the role of HA-CD44/RHAMM signaling in lung carcinogenesis and to assess the potential of triptolide to block HA-CD44/RHAMM signaling and thereby suppress the development and progression of lung cancer. Triptolide reduced the viability of five non-small cell lung cancer (NSCLC) cells, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…We also showed that the interaction between HA and CD44/RHAMM is highly crucial in the proliferation and survival of NSCLC cells and CM generated by fibroblasts induced the proliferation of NSCLC in a HAdependent manner. Also, CM generated by A549 cells and THP-1 The present studies as well as our previous report 20 GlcUA), the substrates of HAS enzymes, could also be a limiting factor for HA synthesis. 21,22 Accumulating evidence indicates that aerobic glycolysis, the hallmark of cancer, increases levels of UDP-GlcNAc 23 and UDP-GlcUA 22 and these effects are under the control of various oncogenic signals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We also showed that the interaction between HA and CD44/RHAMM is highly crucial in the proliferation and survival of NSCLC cells and CM generated by fibroblasts induced the proliferation of NSCLC in a HAdependent manner. Also, CM generated by A549 cells and THP-1 The present studies as well as our previous report 20 GlcUA), the substrates of HAS enzymes, could also be a limiting factor for HA synthesis. 21,22 Accumulating evidence indicates that aerobic glycolysis, the hallmark of cancer, increases levels of UDP-GlcNAc 23 and UDP-GlcUA 22 and these effects are under the control of various oncogenic signals.…”
Section: Discussionsupporting
confidence: 86%
“…The present studies as well as our previous report showed wide variations in the amount of HA secreted by NSCLC cells and the reasons behind these observations are unclear. Although the expression of HAS enzymes is the most important determinant factor for HA synthesis, there was no parallelism between HAS expression and HA secretion, indicating the existence of additional players in the regulation of HA synthesis in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 HAoligosaccharides may act via toll like receptor signaling 27,29,30 or by interfering with the interaction of high molecular weight HA (HMW-HA) and its receptors CD44 and RHAMM. 31,32 Moreover, the relevance of small HA-oligosaccharide products was suggested when Schmaus et al 33 quantified these in tumor interstitial fluids and found a correlation with invasion of tumor cells into lymphatic vessels and the formation of lymph node metastases in colorectal cancer patients. However, recent data suggest that HYAL1 may support tumor metastasis independently of the generation of small HA-oligosaccharide products thus leaving alternative ways of action conceivable.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the target proteins are undefined, it is evident that TPL has some kind of explained effects on the anticancer. However, with the discovery of other mechanisms, TPL can suppress kinases or suggest epigenetic modifications through alkylation (Sun et al, 2017;Zhong et al, 2013;Song et al, 2017;Liu et al, 2017). Chang et al, (2001) have reported that TPL blocked p53-mediated cell cycle arrest to enhance doxorubicin-mediated apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%